Essential Hypertension: Pathophysiology& Management (Current View) - Saxena, Tarun; Ali, Azeema Ozefa; Saxena, Manjari (Cardiology and Cardiovascular Medicine, 2021)
The rising burden of essential hypertension necessitates the need for further understanding of pathophysiology. Recent studies have focused upon sympathetic over-activity. Sympathetic overactivity is associated with increased left ventricular contractility and various mechanisms of hypertension. Disturbed cortical impulses (stress) to the hypothalamus shifts the vasomotor center to a higher level resulting in increased basal sympathetic discharge and hypertension. <gdiv></gdiv>